Application of Ultra-High Performance Concrete in bridge engineering. (20th October 2018) - Zhou, Mi; Lu, Wei; Song, Jianwei; Lee, George C.
Highlights: Forty-two typical and practical applications of UHPC in bridges are introduced. The shortcomings which constrain the application of UHPC are summarized. Potential usages of UHPC for seismic resistance and anti-explosion are predicted. Further researches of UHPC in bridge engineering are proposed. Abstract: Ultra high performance concrete (UHPC) is a type of cement-based composite, which is the most innovative product in concrete technology during the last 30 years. The advantages of UHPC compared with the common concrete, such as superior mechanical performance, excellent anti-seismic property and resistance against environmental degradation are introduced in the paper. The paper begins by briefly introducing its history of development and technical performance. Then, the research and application situation of UHPC in bridge engineering are discussed and many practical applications in bridge bearing component, bridge deck pavement and bridge joints are summarized. Moreover, the paper analyzes advantages and shortcomings of UHPC and the constraints for the application of UHPC in bridge engineering. In addition, the performance of UHPC in seismic resistance and anti-explosion is briefly summarized. Based on these works, prediction of UHPC further research in the future is prospected.